Early Childhood Care and Education Institutions’ Innovative Strategies to Boost Father Participation in Parent Classes - Murniati, Betty; Nurhayati, Sri (Jurnal Ilmiah Profesi Pendidikan, 2024)
This research aims to elucidate the integrative strategies utilized by Early Childhood Care and Education (ECCE) managers in Kecamatan Bandung Kulon to foster fathers' participation in parent classes. Recognizing the pivotal role of fathers in early childhood development, yet acknowledging the barriers they face, this study sought to uncover the methods and strategies ECCE institutions employ. Through a qualitative case study method, interviews with five ECCE managers were conducted as the primary data collection technique. The data was subsequently analyzed using thematic analysis to identify patterns, challenges, and innovative strategies. Findings highlight a confluence of traditional engagements, such as parenting guidance sessions, coupled with innovative tactics like cultural events and flexible scheduling. However, despite these efforts, work-centric challenges and societal expectations remain formidable barriers. This study underscores the imperative for a comprehensive, adaptive, and localized approach in enhancing father involvement in ECCE, adding a valuable dimension to the discourse on inclusive early education.